Comparative study of autograft or allograft in primary anterior cruciate ligament reconstruction - Kustos, T. (Springer-Verlag, 2004)
Between December 1996 and December 2002, we treated 79 patients with arthroscopy-assisted anterior cruciate ligament (ACL) reconstructions. In 53 patients we used autografts and in 26 patients allografts. Patients were followed up for 38 (12–72) months. The two groups did not differ in preoperative sport activity level. The postoperative Lysholm score was 89.9±8.1 in the autograft group and 84.1±18.6 in the allograft group. Comparing the patients’ Lysholm score according to whether they had a low (1–5) or a high (6–10) postoperative Tegner score, we found no statistically significant difference between the groups. On one occasion, the allograft ruptured during the implantation procedure just prior to the fixation. Postoperatively, we performed three revisions—two in the allograft group and one in the autograft group—and three second-look arthroscopies. There were no bacterial infections and no cases of viral transmission. No immune rejection, resorption, or immunsynovitis occurred during the follow-up.